Identifying Critical Criteria on Assessment of Sustainable Materials for Construction Projects in New Zealand Through the Analytic Hierarchy Process (AHP) Approach - Jiachen Qian; Chandana Siriwardana; Wajiha Shahzad (Buildings)
New Zealand’s goal of achieving net-zero greenhouse gas emissions (GHG) by 2050 highlights the urgent need for integrating sustainable practices into the construction industry. Since the construction industry makes a major contribution to GHG emissions, this study aims to address this need by identifying and prioritizing the critical criteria relevant to the effective selection of sustainable construction materials for New Zealand’s construction industry. The research employs a multi-stage approach, including a comprehensive literature review, expert interviews, and industry surveys. Initially, 80 criteria were identified through the literature review. Subsequently, expert interviews and industry surveys led to the identification of 30 critical criteria, which were categorized into environmental, technical, economic, and social impacts, and were ranked based on their importance. This study utilizes a 5-point importance index and Analytic Hierarchy Process (AHP) to rank these criteria. This study notably integrates technical impacts with the three traditional sustainability pillars—environmental, economic, and social—providing a nuanced evaluation of construction material selection. The results indicate that environmental and technical criteria received the highest priority weights (32% each), followed by economic (19%) and social impacts (17%). The findings offer valuable insights for industry stakeholders, assisting them in applying these critical criteria to improve material selection practices in alignment with New Zealand’s sustainability objectives.